Reducing Peripheral Inflammation with Infliximab Reduces Neuroinflammation and Improves Cognition in Rats with Hepatic Encephalopathy - Dadsetan, Sherry; Balzano, Tiziano; Forteza, Jerónimo; Cabrera-Pastor, Andrea; Taoro-Gonzalez, Lucas; Hernandez-Rabaza, Vicente; Gil-Perotín, Sara; Cubas-Núñez, Laura; García-Verdugo, José-Manuel; Agusti, Ana; Llansola, Marta; Felipo, Vicente (Frontiers in Molecular Neuroscience, 2016)
Inflammation contributes to cognitive impairment in patients with hepatic encephalopathy (HE). However, the process by which peripheral inflammation results in cognitive impairment remains unclear. In animal models, neuroinflammation and altered neurotransmission mediate cognitive impairment. Taking into account these data, we hypothesized that in rats with HE: 1) peripheral inflammation is a main contributor to neuroinflammation; 2) neuroinflammation in hippocampus impairs spatial learning by altering AMPA and/or NMDA receptors membrane expression; 3) reducing peripheral inflammation with infliximab (anti-TNF-a) would improve spatial learning; 4) this would be associated with reduced neuroinflammation and normalization of the membrane expression of glutamate receptors. The aims of this work were to assess these hypotheses. We analyzed in rats with portacaval shunt (PCS) and control rats, treated or not with infliximab: a) peripheral inflammation by measuring prostaglandin E2, IL10, IL-17 and IL-6; b) neuroinflammation in hippocampus by analyzing microglial activation and the content of TNF-a and IL-1b, IL-1b), c) AMPA and NMDA receptors membrane expression in hippocampus and d) spatial learning in the Radial and Morris water mazes. We assessed the effects of treatment with infliximab on peripheral inflammation, on neuroinflammation and AMPA and NMDA receptors membrane expression in hippocampus and on spatial learning and memory. PCS rats show increased serum prostaglandin E2, IL-17 and IL-6 and reduced IL-10 levels, indicating increased peripheral inflammation. PCS rats also show microglial activation and increased nuclear NF-kB and expression of TNF-a and IL-1b in hippocampus. This was associated with altered AMPA and NMDA receptors membrane expression in hippocampus and impaired spatial learning and memory in the radial and Morris water maze. Treatment with infliximab reduces peripheral inflammation in PCS rats, normalizing prostaglandin E2, IL-17, IL-6 and IL-10 levels in serum. Infliximab also prevents neuroinflammation, reduces microglial activation, translocates NF-kB into nucleoli and normalizes TNF-a and IL-1b content in hippocampus. This was associated with normalization of AMPA receptors membrane expression in hippocampus and of spatial learning and memory. The results suggest that peripheral inflammation contributes toispatial learning impairment in PCS rats. Treatment with anti-TNF-a could be a new therapeutic approach to improve cognitive function in patients with HE.